PENGELOLAAN EKSPEKTASI WARGA PADA PERENCANAAN PENGADAAN TANAH MELALUI PKM - Rakhmat Haryono; Riffka Fauzany; Hani Hatimatunnisani; Hendriady De Keizer (Jurnal Pengabdian Kepada Masyarakat, 2025)
A community service program (PKM) delivered participatory socialization and dialogue to support land acquisition planning for the rehabilitation of Cipancuh Dam, Indramayu, Indonesia. An intervention-based case study with a participatory, mixed-methods approach was applied to improve residents’ understanding of rehabilitation objectives, land acquisition planning stages, parcel listing–measurement–verification activities, and stakeholders’ rights and obligations. Forum findings highlighted recurring concerns regarding compensation, corporate social responsibility, and irrigation service distribution. Therefore, procedural clarification and accessible feedback/grievance channels are pivotal to strengthening social acceptance and preventing early-stage conflicts during land acquisition planning.